MODERN METHODS OF DIAGNOSING COMPLICATIONS IN THE PULMONARY ARTERY ОN COMORBID STATE OF RESPIRATORY DISEASES (Novateur Publications, 2023)
The tutorial possible fully and systematically reflected contemporary information about the etiology, pathogenesis, classification, clinic and diagnosis of PAH, the correct interpretation of which is the key not only accurate clinical diagnosis, but also adequate for individual selection of optimal therapies. Advances in modern medicine, the introduction in clinical practice of medicine principles of evidence, a significant expansion of the arsenal of medicinal drugs require treatment from a doctor a good knowledge of the pharmacodynamics and pharmacokinetics of the main groups of drugs used in diseases of the cardiovascular and bronchi pulmonary system.